Cast from bells - Hancock, Suzanne, 1971- (Hugh MacLennan poetry series, 2010)
"During the Second World War, bells throughout Europe were taken from their towers and used to make munitions. At the end of the war, many of the bells were recast and restored to their heights. In Cast from Bells, Suzanne Hancock dramatizes how the same substance in one form gathers a crowd with its ringing, but in another shape scatters people and creates disorder." "Balancing the bells of the past with the personal life of the present, these poems offer an intimate look at a woman leaving her husband. Against the backdrop of history, honest glimpses of a relationship's ruin reveal surprising connections between the exalted and mundane." "Cast from Bells tells a story about people and things dividing and uniting, and the sounds and spaces between bells and bullets."--Jacket